The impact of the Chinese cornstarch futures on spot market and corn futures market - Crentsil Kofi Agyekum; Haifeng Huang; Jianshu Chen (Cogent Economics & Finance, 2017)
This article investigates price transmission mechanism and volatility impact between Chinese cornstarch futures market and relevant markets through Johansen cointegration test, VEC model and GARCH model. The empirical results indicated that the Chinese cornstarch futures price could guide cornstarch spot price uni-directionally and there are long-term cointegration relationships between them. There is a co-integration and bi-directional lead relationship between cornstarch futures price and corn futures price. The launch of cornstarch futures market can slightly reduce volatility of domestic corn futures market. However, the launch of cornstarch futures market has no significant impact on the spot market.
Keywords: 330; cornstarch futures; spot price; price transmission; volatility